Sosialisasi Personal Higiene pada Pedagang Ikan Panggang di Kawasan Wisata Kuliner Loang Baloq, Mataram - Mutia Devi Ariyana; Nazaruddin Nazaruddin; Baiq Rien Handayani; Sri Widyastuti; Moegiratul Amaro (Jurnal SIAR ILMUWAN TANI, 2021)
Loang Baloq is currently a culinary center for grilled fish that has development prospects to support regional tourism. However, the behavior and habits of the grilled fish sellers who do not pay attention to the personal hygiene aspects have resulted in the low quality of the grilled fish, especially from the microbiological aspect. The main problem of sellers as a target of this community service activity was the lack of their knowledge related to personal hygiene procedures and the risks from food safety perspective that can be caused if personal hygiene procedures were not applied in the processing of grilled fish. In this activity, several solutions were given to improve the quality and safety of grilled fish at Loang Baloq including education to the seller, a person who are directly involved in all production stages, about the importance of personal hygiene application, the risk of not applying personal hygiene, types of personal hygiene standart equipment for food processing and personal hygiene procedures, especially how to wash hands properly. Activities were carried out by lecture method, question and answer (FAQs) and direct practice. The reflection result showed that this activity improving the sellers knowledges including the meant of personal hygiene and the importance of applying personal hygiene in grilled fish processing, the types of personal hygiene standard equipment for food processors and how to use them, and helped the sellers practice how to wash their hands properly.